Plasma exchange alone versus combination with intravenous immunoglobulin/methylprednisolone pulse therapy in severe systemic rheumatic diseases: a retrospective study - Guo, Jing; Li, Shuiwen; Xu, Hao; Wang, Xinxin; Luo, Weiyuan; Sun, Jie; Li, Jianhua; Chen, Zhu; Lu, Guiyang; Huang, Xiaolong; Chen, Shiju; Ning, Yaogui (Frontiers in Immunology, 2024)
BackgroundFor severe systemic rheumatic diseases (SRDs), therapeutic plasma exchange (TPE) may be applied as a rescue therapy; it usually combined with intravenous immunoglobulin (IVIG) or intravenous methylprednisolone pulse (IVMP) in severe SRDs. However, the necessity of this combination treatment strategy in SRDs remains uncertain.ObjectiveThis retrospective study aimed to evaluate the effectiveness of TPE alone versus TPE combined with IVIG/IVMP in treating severe SRDs.MethodsPatients with severe SRDs treated with TPE who were admitted to the department of intensive care unit (ICU) from January 2011 to December 2019 were included. These patients were divided into two groups: the TPE-alone group (TPE group) and the TPE plus IVIG/IVMP group (TPE + IVIG/IVMP group). The patients’ clinical characteristics, the Sequential Organ Failure Assessment score, the 28-day mortality rate, and the length of ICU stay were evaluated in the two groups.ResultsNinety-one patients were enrolled in this study: 51 patients in the TPE group and 40 patients in the TPE + IVIG/IVMP group. In the TPE group, the median age was 51.39 ± 15.34 years, and 64.71% were women. In the TPE + IVIG/IVMP group, the median age of the patients was 42.93 ± 16.56 years, and 75% were women. The infection rate in the TPE + IVIG/IVMP group was significantly higher than that in the TPE group (P < 0.05). Both the 28-day mortality and the length of ICU stay did not differ statistically between the two groups (P > 0.05).ConclusionThis study showed no benefit of combing IVIG/IVMP with TPE in improving the outcome of patients with severe SRDs, suggesting that IVIG/IVMP may not be necessary when used conjunction with TPE for the treatment of severe SRDs.